ECG Changes in 8-Year-Old Boy with Pulmonary Edema after Head Injury - Bojko Bjelakovic; Vladislav Vukomanovic; Ljiljana Saranac; Ivan Stefanovic (The Scientific World Journal)
This is a case story of an 8-year-old boy with no prior history of cardiac disease who developed acute pulmonary edema with ECG changes similar to transmural myocardial infarction after basilar skull fracture. Biochemical evaluation showed elevated total creatine kinase activity –1,350 U/L with 12% MB isoenzyme fraction. The brain scan on admission showed cerebral edema with ethmoidal sinuses hemorrhage. Neurogenic pulmonary edema following CNS damage is an extremely rare entity in the pediatric population and there are few reports. There are many proposed mechanisms and explanations of its origin. Based on previous reports and experimental studies, the cause of “neurogenic” pulmonary edema may be of cardiac as well as of noncardiac origin.